Karakterisasi Bakteri Penghasil Gas Metana pada Rumput Laut Jenis Gracilaria sp - Erwin F Silalahi; Melki .; Heron Surbakti (Maspari Journal : Marine Science Research, 2012)
One of the biological resources that have importanteconomic value is seaweed. During this  seaweed  is  only  used  as  a  source  of  food,  medicines  and  cosmetics.  The  many  types  of seaweed  that  untapped  potential  as  an  alternative  to  bioenergy-producing  raw  materials. Increasing energy demand, caused by population growth and depletion of oil reserves as well as emissions from fuel problems put pressure on people to produce and use renewable energy is an  alternative  biogas  from  seaweeds.  The  purpose  of this  study  was  to  determine  the  gas pressure and to know the characterization of bacteria methane-producing bacteria of seaweed speciesGracilaria sp. This research is a laboratory scale research.The research was conducted in  July  2010  to  March  2011.  The  sampling  was  taken  around  the  waters  Kalianda,  South Lampung.  Making  biogas  process  is  conducted  at  the  Laboratory  of  Marine  Science. Characterization of bacteria is conducted at the Central Health Laboratory Palembang. Biogas manufacturing  done  by  collecting  seaweed  and  coastal  sediments  asseedsman  intake  that  is the source of microorganisms that later would form  the metan gas in the process of anaerobic fermentation  of  seaweed,  the  completion  of  the  stater  and  the  digester  and  manufacturing fields,  biogas pressure observations carried  out by  using  the manometer.  Characterization  of bacteria consists of three stages namely the characterization of morphology, macroscopic and physiological  observations. Based on research results  obtained  gas  pressure type  of  seaweed Gracilaria sp produced 14.88 Psi. Morphological characteristics of bacterial cells is a group of gram negative.ABSTRAKSalah  satu  sumberdaya  hayati  yang  mempunyai  nilai  ekonomis  penting  adalah rumput  laut.  Selama  ini  rumput  laut  hanya  dimanfaatkan  sebagai  sumber  makanan,  obatobatan  dan  kosmetik.  Peningkatan  permintaan  energi, yang  disebabkan  oleh  pertumbuhan populasi penduduk dan menipisnya sumber cadangan minyak serta permasalahan emisi dari bahan  bakar  memberikan  tekanan  kepada  masyarakat  untuk  memproduksi  dan menggunakan energi terbaharukan yaitu biogas alternatif dari rumput laut. Tujuan penelitian ini adalah untuk mengetahui tekanan gas serta mengetahui karakterisasi bakteri penghasil gas  metan  rumput  laut  jenis  Gracilaria sp.  Penelitian  ini  merupakan  penelitian  skala laboratorium. Penelitian ini dilaksanakan pada Bulan Juli 2010 sampai dengan Maret 2011. Pengambilan  sampel  diambil  di  sekitar  perairan  Kalianda,  Lampung  Selatan.  Proses Pembuatan  biogas  dilakukan  di  Laboratorium  Dasar  Ilmu  Kelautan.  Karakterisasi  Bakteri dilakukan di Balai Besar Laboratorium Kesehatan Palembang. Pembuatan biogas dilakukan dengan  cara  pengumpulan  rumput  laut  dan  pengambilan sedimen  pantai  sebagai  penyemai yaitu  sumber  mikroorganisme  yang  nantinya  akan  membentuk  gas  metan  dalam  proses fermentasi anaerob rumput laut, kemudian penyiapan  digester serta pembuatan starter dan isian, pengamatan  tekanan  biogas  dilakuakan  dengan  menggunakan  manometer. Karakterisasi bakteri terdiri dari tiga  tahap  yaitukarakterisasi morfologi,  makroskopis dan pengamatan fisiologi. Berdasarkan hasil penelitian didapatkan tekanan gas jenis rumput laut Gracilaria sp  dihasilkan 14,88 Psi. Karakteristik morfologi sel  bakteri merupakan kelompok dari gram negatif.